2017
DOI: 10.1136/jclinpath-2017-204478
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of computer-aided diagnosis (CADx) of breast pathology using immunohistochemistry results of core needle biopsy samples for synaptophysin, oestrogen receptor and CK14/p63 for classification of epithelial proliferative lesions of the breast

Abstract: The CADx system was able to analyse sufficient data for all types of epithelial proliferative lesions of the breast including invasive breast cancer. This system may be useful for pathological diagnosis of breast CNB in routine investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…For pathologists, immunostaining (IHC) can accurately locate the site of organization and is an auxiliary method for diagnosing BC. IHC analysis of breast tumours has advantages in the following four aspects: (a) can distinguish between benign and malignant breast tumours; (b) can assess interstitial infiltration; (c) can distinguish between ductal and lobular tumours; and (d) can detect expression of proteins associated with BC treatment and prognosis, to guide endocrine therapy and prognosis 98‐101 . At present, IHC is the best diagnostic method for oestrogen receptor (ER) and progesterone receptor (PR) in BC 102 .…”
Section: Molecular Biotechnology Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…For pathologists, immunostaining (IHC) can accurately locate the site of organization and is an auxiliary method for diagnosing BC. IHC analysis of breast tumours has advantages in the following four aspects: (a) can distinguish between benign and malignant breast tumours; (b) can assess interstitial infiltration; (c) can distinguish between ductal and lobular tumours; and (d) can detect expression of proteins associated with BC treatment and prognosis, to guide endocrine therapy and prognosis 98‐101 . At present, IHC is the best diagnostic method for oestrogen receptor (ER) and progesterone receptor (PR) in BC 102 .…”
Section: Molecular Biotechnology Examinationmentioning
confidence: 99%
“…Aberrant methylation of RhoBTB2 gene may affect expression of the RhoBTB2 gene, which influences PR protein status, become the factor that induce BC endocrine therapy and prognosis. [98][99][100][101] At present, IHC is the best diagnostic method for oestrogen receptor (ER) and progesterone receptor (PR) in BC. 102 The basic principle of IHC (as shown in Figure 7) is antigen-specific binding of antibodies, and these antibodies are usually labelled with colour reagents (such as fluorescein and metal ion) to detect the antigen, protein, peptides, etc IHC can screen and diagnose BC patients by evaluating the level of marker proteins.…”
Section: Rhobtb2mentioning
confidence: 99%
“…In the field of breast cancer, the current artificial intelligence technology is mainly used in early imaging screening (6)(7)(8), and pathologists use virtual microscopes and remote pathological digital section consultations (9). Maeda and other studies used 200 hollow-core needle biopsy breast specimens to perform immunohistochemical staining on their estrogen receptor (ER), synaptophysin, and CKl4/p63, scan the whole section, and analyze the nuclear and cytoplasmic staining with image analysis software as proof of diagnosis cases with high ER expression may indicate malignancy (10).…”
Section: Figure 10mentioning
confidence: 99%
“…Recently, research regarding convolutional neural networks (CNNs) for CAD has expanded to include chest X-rays, computed tomography (CT), and high-resolution CT (HR-CT) [3]. Furthermore, several studies have investigated the application of CAD based on magnetic resonance imaging (MRI) and functional MRI, as well as ultrasound images, infrared thermography, electroencephalography (EEG), digital histopathology, and endoscopy photographs [4,5,6,7]. Previous research has demonstrated that CAD is useful for diagnosing [8] and characterizing patterns [9] of tuberculosis, with decent diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%